A regionalização do agronegócio da soja em Rondônia - Silva, Ricardo Gilson da Costa (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
The advance of soy agribusiness in the Brazilian Amazon Region is a result of the agricultural modernization processes which derivates of the Capital in rural spaces. In the south of Rondonia, the productive regionalization of soy modifies the rural- -urban relations and constitutes the corporative use of the territory by the hegemo- nic corporations of agribusiness. The reduction of the population in the rural areas and the enlargement of the cities are geographical impacts of this process which fragments the Rondonia’s spaces from the production of its commodity.